Research progress on the clinical application and mechanism of iguratimod in the treatment of autoimmune diseases and rheumatic diseases - Long, Zhiyong; Zeng, Liuting; He, Qi; Yang, Kailin; Xiang, Wang; Ren, Xiang; Deng, Ying; Chen, Hua (Frontiers in Immunology, 2023)
Autoimmune diseases are affected by complex pathophysiology involving multiple cell types, cytokines, antibodies and mimicking factors. Different drugs are used to improve these autoimmune responses, including nonsteroidal anti-inflammatory drugs (NSAIDs), corticosteroids, antibodies, and small molecule drugs (DMARDs), which are prevalent clinically in the treatment of rheumatoid arthritis (RA), etc. However, low cost-effectiveness, reduced efficacy, adverse effects, and patient non-response are unattractive factors driving the development of new drugs such as iguratimod. As a new disease-modifying antirheumatic drug, iguratimod has pharmacological activities such as regulating autoimmune disorders, inflammatory cytokines, regulating immune cell activation, differentiation and proliferation, improving bone metabolism, and inhibiting fibrosis. In recent years, clinical studies have found that iguratimod is effective in the treatment of RA, SLE, IGG4-RD, Sjogren ‘s syndrome, ankylosing spondylitis, interstitial lung disease, and other autoimmune diseases and rheumatic diseases. The amount of basic and clinical research on other autoimmune diseases is also increasing. Therefore, this review systematically reviews the latest relevant literature in recent years, reviews the research results in recent years, and summarizes the research progress of iguratimod in the treatment of related diseases. This review highlights the role of iguratimod in the protection of autoimmune and rheumatic bone and related immune diseases. It is believed that iguratimod’s unique mode of action and its favorable patient response compared to other DMARDs make it a suitable antirheumatic and bone protective agent in the future.